Development of an indicator system for multi-point trigger surveillance and early warning of infectious diseases: a Delphi study - Tingyu ZHANG; Yanhui LIU; Ying LU; Mengmeng MA; Xiao ZHANG; Yilan LI; Junxi LI; Pengzhe QIN; Jun YUAN (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo establish an indicator system for multi-point trigger surveillance and early warning of infectious diseases, providing valuable evidence to improve the overall prevention and control framework. MethodsThe pool of indicators was initially developed through a literature review and focus group discussions, followed by two rounds of Delphi expert consultations with 21 experts nationwide. Based on the experts' ratings of the importance, usability and familiarity of the indicators, the indicators were screened, statistically analyzed and their final weights determined. ResultsThe positive coefficients of experts in the two rounds of consultation were both 100%, the authority coefficients of experts were both ≥ 0.79, and the coordination coefficients of expert opinions were 0.34 - 0.46 (all P < 0.001). According to the occurrence and development process of infectious diseases and the requirements of related multi-source data fusion and collision, the indicator system was divided into three dimensions: single-source data, multi-source data fusion and risk factors. Finally, 82 indicators for multi-point trigger surveillance and early warning of infectious diseases were established. ConclusionThe index system developed in this study for multi-point trigger surveillance and early warning of infectious diseases is based on sound scientific principles and reasoning. It has the potential to expand the channels of infectious disease monitoring and achieve multi-point trigger surveillance and early warning.